Age‐related white matter changes revealed by a whole‐brain fiber‐tracking method in bipolar disorder compared to major depressive disorder and healthy controls. Issue 2 (9th November 2020) - Masuda, Yoshikazu; Okada, Go; Takamura, Masahiro; Shibasaki, Chiyo; Yoshino, Atsuo; Yokoyama, Satoshi; Ichikawa, Naho; Okuhata, Shiho; Kobayashi, Tetsuo; Yamawaki, Shigeto; Okamoto, Yasumasa
Abstract : Aim: Several studies have reported altered age‐associated changes in white matter integrity in bipolar disorder (BD). However, little is known as to whether these age‐related changes are illness‐specific. We assessed disease‐specific effects by controlling for age and investigated age‐associated changes and Group × Age interactions in white matter integrity among major depressive disorder (MDD) patients, BD patients, and healthy controls. Methods: Healthy controls ( n = 96; age range, 20–77 years), MDD patients ( n = 101; age range, 25–78 years), and BD patients ( n = 58; age range, 22–76 years) participated in this study. Fractional anisotropy (FA) derived from diffusion tensor imaging in 54 white matter tracts were compared after controlling for the linear and quadratic effect of age using a generalized linear model. Age‐related effects and Age × Group interactions were also assessed in the model. Results: The main effect of group was significant in the left column and body of the fornix after controlling for both linear and quadratic effects of age, and in the left body of the corpus callosum after controlling for the quadratic effect of age. BD patients exhibited significantly lower FA relative to other groups. There was no Age × Group interaction in the tracts. Conclusion: Significant FA reductions were found in BD patients after controlling for age, indicating that abnormal white matter integrity in BD may occur at a younger age rather than developing progressively with age.